Value-Oriented Model of Human Capital Development in Islamic Schools: Integrating Islamic Ethics and Total Quality Management - Nurfuadi Nurfuadi; Nurkholis; Slamet Yahya; Asdlori Asdlori; Rahman Afandi; Sofia Nur; Asnee Doloh (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
Strategic human capital development (HCD) in Islamic schools must align with national education policies and Islamic ethical principles, yet this integration remains underexplored in the literature. This study employs a qualitative case study design at SMA IT Nurul Ihsan Boarding School, Cilacap, Indonesia, to examine how Islamic ethics are systematically integrated with Total Quality Management (TQM) in human capital development practices. Data were collected through in-depth interviews, observation, and institutional documentation, and analyzed using triangulation techniques to ensure credibility and validity. The findings reveal a value-oriented HCD model grounded in three interrelated dimensions: ethical-spiritual foundation (amanah, ihsan, and hisbah), participatory-transformative leadership, and systematic quality control mechanisms. The integration of Islamic ethical values with TQM principles is operationalized through structured evaluation systems, technology-assisted supervision (including geolocation-based attendance), incentive policies, and spiritual mentoring programs. This model differs from conventional HCD frameworks by explicitly embedding Islamic moral accountability within strategic quality management processes. Despite challenges such as limited qualified staff, time constraints, and alignment issues with policies, the model enhances institutional effectiveness, competitiveness, and sustainability. The study contributes a conceptual framework for value-oriented human capital development in Islamic education and offers practical insights for leadership reform and future research in faith-based educational management.